2016
DOI: 10.15740/has/ijpp/9.2/551-555
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of thiamethoxam 25 per cent WG against major insect pests of rice (Oryza sativa L.)

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…Similar results were confirmed in the field experiment II conducted during rabi 2019-2020, with the least incidence being with thiamethoxam followed by that of garlic and chilli extract. These results are in conformity with those of Panse et al (2016) who reported that thiamethoxam 25WG @ 50g a.i./ ha recorded less deadhearts. Rani (2013) reported that garlic and chilli extract at 5 and 10% did not allow the entry of stem borer larvae in rice stalks up to 6 and after 36 hr of release with a maximum antifeedant efficacy.…”
Section: Resultssupporting
confidence: 93%
“…Similar results were confirmed in the field experiment II conducted during rabi 2019-2020, with the least incidence being with thiamethoxam followed by that of garlic and chilli extract. These results are in conformity with those of Panse et al (2016) who reported that thiamethoxam 25WG @ 50g a.i./ ha recorded less deadhearts. Rani (2013) reported that garlic and chilli extract at 5 and 10% did not allow the entry of stem borer larvae in rice stalks up to 6 and after 36 hr of release with a maximum antifeedant efficacy.…”
Section: Resultssupporting
confidence: 93%